The role of female teachers in addressing the behavioral problems among the female primary students at the city of Abha from the point of view of female leaders of primary schools. (Journal Of Educational and Psychological Researches, 2024)
This study aimed to identify the role of female teachers in addressing the problem of aggressive behavior and the problem of lying among female primary students from the point of view of primary school leaders, to identify the obstacles faced by the female teachers of primary schools in addressing behavioral problems from the point of view of female leaders of primary schools.The study used the descriptive survey approach, and applied a questionnaire to the entire population of the study, which consisted of (82) female leaders in primary schools in the city of Abha.The study found that: The female teachers play their role in addressing the problems of aggressive behavior among primary school students with a very high degree from the point of view of primary school leaders, with an arithmetic mean of (4.38). The female teachers play their role in addressing the problem of lying among primary school students with a very high degree from the point of view of primary school leaders, with an arithmetic mean of (4.43). The female leaders of primary schools agreed with a high degree to the obstacles faced by primary school teachers in addressing the behavioral problems, with an arithmetic mean of (3.76).